Short- and long-term impact of adapted physical activity and diet counseling during adjuvant breast cancer therapy: the “APAD1” randomized controlled trial - Marion Carayol; Gregory Ninot; Pierre Senesse; Jean-Pierre Bleuse; Sophie Gourgou; Hélène Sancho-Garnier; Chakib Sari; Isabelle Romieu; Gilles Romieu; William Jacot (BMC Cancer, 2019)
Abstract Background Patients with breast cancer undergoing chemotherapy and radiotherapy experience fatigue and other treatment side effects. Integrative therapies combining physical activity and dietary counseling are recommended; however to date no large randomized controlled trial has been conducted during adjuvant therapy. The Adapted Physical Activity and Diet (APAD) intervention was evaluated for its ability to decrease fatigue (primary outcome), anxiety, depression, body mass index (BMI), and fat mass, and enhance muscular and cognitive performances, and quality-of-life (QoL). Methods Women diagnosed with early breast cancer (N = 143, mean age = 52 ± 10 years) were randomized to APAD or usual care (UC). APAD included thrice-weekly moderate-intensity mixed aerobic and resistance exercise sessions and 9 dietetic consultations. Patient-reported outcomes (PROs) and anthropometric, muscular, and cognitive variables were measured at baseline, 18 weeks (end of chemotherapy), and 26 weeks (end of radiotherapy and intervention), and at 6- and 12-month post-intervention follow-ups. Multi-adjusted linear mixed-effects models were used to compare groups over time. Results Significant beneficial effects of the APAD intervention were observed on all PROs (i.e., fatigue, QoL, anxiety, depression) at 18 and 26 weeks. The significant effect on fatigue and QoL persisted up to 12-month follow-up. Significant decreases in BMI, fat mass, and increased muscle endurance and cognitive flexibility were observed at 26 weeks, but did not persist afterward. Leisure physical activity was enhanced in the APAD group vs UC group at 18 and 26 weeks. No significant effect of the intervention was found on major macronutrients intake. Conclusions A combined diet and exercise intervention during chemotherapy and radiotherapy in patients with early breast cancer led to positive changes in a range of psychological, physiological and behavioral outcomes at the end of intervention. A beneficial effect persisted on fatigue and QoL at long term, i.e., 1 year post-intervention. Diet-exercise supportive care should be integrated into the management of early breast cancer patients. Trial registration The APAD study was prospectively registered on ClinicalTrials.gov (NCT01495650; date of registration: December 20, 2011).